2016
DOI: 10.1042/bst20160107
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the exoribonucleases DIS3L2 and XRN1 in human disease

Abstract: RNA degradation is a vital post-transcriptional process which ensures that transcripts are maintained at the correct level within the cell. DIS3L2 and XRN1 are conserved exoribonucleases which are critical for the degradation of cytoplasmic RNAs. Although the molecular mechanisms of RNA degradation by DIS3L2 and XRN1 have been well studied, less is known about their specific roles in development of multicellular organisms or human disease. This review focusses on the roles of DIS3L2 and XRN1 in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…DIS3L2 preferentially recognizes mRNAs with short poly(U)-tracts at their 3 0 end that are added by poly(U) polymerases (PUPs) like TUT4/7 (Viegas et al 2015). Intriguingly, DIS3L2 has been linked to apoptosis (Thomas et al 2015), and mutations in DIS3L2 are associated with Perlman syndrome (Pashler et al 2016). These observations further underscore the biological and developmental importance of this 3 0 -to-5 0 exoribonuclease.…”
Section: The Major Steps and Mechanisms Of Mrna Decay In Eukaryotesmentioning
confidence: 85%
“…DIS3L2 preferentially recognizes mRNAs with short poly(U)-tracts at their 3 0 end that are added by poly(U) polymerases (PUPs) like TUT4/7 (Viegas et al 2015). Intriguingly, DIS3L2 has been linked to apoptosis (Thomas et al 2015), and mutations in DIS3L2 are associated with Perlman syndrome (Pashler et al 2016). These observations further underscore the biological and developmental importance of this 3 0 -to-5 0 exoribonuclease.…”
Section: The Major Steps and Mechanisms Of Mrna Decay In Eukaryotesmentioning
confidence: 85%
“…Xrn1/XRN1 has been associated with human pathologies such as osteosarcoma and infectious diseases [80,81] and even virus infection in yeast [82,83]. Thus, the cell must strictly modulate autophagy at multiple levels to prevent disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While XRN1 is described as a general decay factor, there is evidence that 5' decay shows some specificity in vivo. Indeed, in Drosophila, mutations in XRN1 have specific phenotypes, including wound healing, epithelial closure and stem cell renewal in testes, suggesting that it specifically degrades a subset of mRNAs [51]. Most importantly, a recent study showed that yeast XRN1 associates with ribosomes and decays mRNAs during translation [52].…”
Section: Distinct Decay Pathwaysmentioning
confidence: 99%